The influence of parent control structure on parent conflict in Vietnamese international joint ventures: an organizational justice-based contingency approach - Barden,Jeffrey; Steensma,K.; Lyles,M. (Journal of International Business Studies, 2005)
There has been significant interest in understanding how the distribution of parental control over international joint ventures (IJV) influences IJV outcomes (e.g., parent conflict, survival, performance). Yet, the accumulation of research on the relationship between control structure and IJV outcomes has been somewhat inconclusive and even contradictory. We contribute to this research stream by developing an organizational justice-based contingency model relating parental control structure to parent conflict. We suggest that the level of conflict between IJV parents will depend on the consistencies between the control structure and parents' contribution of proprietary resources, and between control structure and the parents' abilities to effectively monitor operations. Our analysis of Vietnamese joint ventures provides some support for our model, and suggests that the relationship between parent control structure and IJV outcomes is perhaps more complex than previously thought.
Keywords: Strategy & Entrepreneurship